PENGARUH PERMAINAN TRADISIONAL KELOMPOK TERHADAP KETERAMPILAN SOSIAL ANAK DI TK NEGERI 48 BUKIT MAKMUR - Napiqoh Napiqoh; Atika Wirdasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social skills are essential in early childhood development because they support children's ability to cooperate, communicate, share, follow rules, regulate themselves, and show empathy toward peers. This study aimed to analyze the effect of group-based traditional games on children's social skills at TK Negeri 48 Bukit Makmur. The study used a quantitative approach with a quasi-experimental one group pretest-posttest design. The participants were 36 children divided into three learning groups, with 12 children in each group. The intervention consisted of group-based traditional games, including simplified gobak sodor, ular naga, team engklek, boy-boyan, mini bakiak, and group jump rope, implemented in eight sessions. The research instrument was a social skills observation sheet using a 1-4 rating scale covering cooperation, communication, sharing, rule compliance, self-control, and empathy. The results indicated that children's mean social skills score increased from 58.58 in the pretest to 80.62 in the posttest. The paired sample t-test showed t(35)=35.61 and p<0.001, with an N-Gain score of 0.54 in the medium category and Cohen's dz of 5.93. These findings suggest that group-based traditional games positively influence children's social skills. Group-based traditional games are recommended as a contextual, enjoyable, and effective play-based learning strategy to stimulate early childhood social development.